The relevance of home-grown rubrics for online communicative assessment in an Islamic institution during the pandemic - Roszalina, Abdul Rahim; Nor Yazi, Khamis; Hafizoah, Kassim; Shuhada, Mustafa Hilmi (Universiti Malaysia Pahang, 2024)
Assessing English communicative abilities within an online environment poses challenges, particularly when aligning assessment instrument rubrics to enhance the evaluation process and learning outcomes. Home-grown rubrics (HGR) can address specific situations where standardised rubrics might only partially meet an assessment's goals or unique requirements. However, several challenges associated with HGR have been identified when assessing complex skills such as communication. These include inconsistencies in rubric design, limitations in capturing subjective aspects of performance, and difficulties in providing coherent, actionable feedback. This study investigates the relevance of HGR assessment rubrics for English communication skills to cater to online contexts, primarily during the pandemic. An explanatory sequential mixed-methods design focused on an Islamic institution’s English for Proficiency (Pre-Intermediate) course was used to gather data from students for quantitative analysis and from instructors for qualitative inquiries after using the HGR for a semester. A survey instrument with scales of agreement was adapted, piloted, and distributed to 87 students. An unstructured interview was chosen to uncover in-depth insights from four lecturers actively involved with the HGR. Descriptive and thematic analyses were employed to determine users’ perceived agreement and experiences in developing and utilising the HGR. Findings indicate that the students accepted the HGR as a tool for self-assessing their English communicative abilities in a virtual environment. The HGR has also enhanced both lecturers’ and students’ awareness of the assessment process, improved the efficiency of online assessments, and helped students focus on critical components of their assessments. The outcome substantiates the relevance of the HGR for the studied context, suggesting its broader applicability and tailor-made design for other online English language courses and skills.